Antibacterial Effect of Starfruit Extract (Averrhoa blimbi L.) against Streptococcus mutans - Purba, Member Reni; Dian Soraya Tanjung; Ilma Al Halifa Hasibuan (HM Publisher, 2024)
Dental caries is caused by gram-positive bacteria Streptococcus mutans, which is part of the normal flora of the mouth. Herbal medicines have powerful antibacterial compounds that can be used to limit the growth of germs that cause infections. The aim of the research was to determine whether starfruit extract (Averrhoa blimbi L.) has antibacterial properties against Streptococcus mutans. This type of research uses a posttest only control group design in the laboratory. Streptococcus mutans in pure culture were used as the research sample. This study had two control groups, one with four repetitions of DMSO as a negative control and one with a positive control (0.2% chlorhexidine), and four treatment groups with starfruit extract concentrations (20%, 40%, 60%, and 80 %). The disc diffusion method was used to test the antibacterial effect. One-way ANOVA and post hoc LSD statistical tests were then used to test the results. The results showed that, for Streptococus mutans bacteria, the mean and standard deviation of the diameter of the inhibition zone of starfruit extract at concentrations of 20%, 40%, 60%, and 80% were 12.03 ± 0.33 mm, 16.70 ± 0, 48 mm, 19.98 ± 0.13 mm, 22.25 ± 0.26 mm, and 19.25 ± 0.91 mm in the positive control, but no zone of inhibition was observed in the negative control. The width of the inhibition zone in starfruit extract (Averrahoa blimbi L.) at doses of 20%, 40%, 60%, 80%, positive control, and negative control was significantly different, according to the results of the one-way ANOVA test (p=0.000; p≤ 0.05). Antibacterial efficacy against Streptococcus mutans varied significantly (p≤0.05) among all star fruit extract groups and positive and negative controls, based on LSD post hoc test findings. Based on the research results, it can be said that star fruit extract at the most effective concentration, namely 80%, has antibacterial properties against Streptococcus mutans.